PENGUATAN PENDIDIKAN KARAKTER DI SD IT INSAN TELADAN MANDIRI CIBITUNG - Muttaqin, Muhammad Fauzan; Aviari, Bella Alifia (JIEGC Journal of Islamic Education Guidance and Counselling, 2022)
This study aims to see the role of schools, especially teachers, in strengthening the character of students, especially in elementary schools. And see what schools and teachers are doing in terms of character building of students in elementary schools. This research was conducted using descriptive qualitative research methods, as well as data collection by means of observation combined with interviews and documentation. Data analysis techniques used triangulation techniques and sources. Based on the results of the study, the PPK conducted by the school on students to develop religious, nationalist, independent, mutual cooperation and good integrity character. Students also participate in every character development activity carried out by the school in an orderly manner.